City Resilience Vs. Resilient City: Terminological Intricacies and Concept Inaccuracies - Mierzejewska, Lidia; Wdowicka, Magdalena (Quaestiones Geographicae, 2018)
The concept of resilience has in recent years been one of the more commonly used urban development concepts. In the social sciences, the term is understood as a dynamic process that reflects a relatively good adaptation, irrespective of the hazards or traumatic experiences. It is linked with the concepts of risk, vulnerability and positive adaptation. The concept of resilience as used in the social sciences has been adapted by other disciplines, including research on the city, where the term is ambiguously and sometimes inconsistently defined. The aim of this study is to explain the term resilience, its reference to the city and to clear up ambiguities of the terminology related to the two lines of research on resilience in relation to the city as presented by the relevant literature: city resilience and the resilient city. Analyses show that both these terms, despite their widespread application, are at present imprecisely defined in the relevant literature and generally speaking used interchangeably, which makes their precise application difficult. In addition, the assumption that city resilience can be treated as a process that leads to a desired state of the resilient city, has not been confirmed. The correctness of the application of the second of these concepts (the resilient city) raises doubts, because it will probably never be possible to develop a city not vulnerable or fully resistant to various types of development perturbations.